Optimization and kinetics of biodiesel production from soybean oil using new tetraethylammonium ionic liquids with amino acid-based anions as catalysts. (15th September 2022) - Wang, Xiaohang; Yang, Kun; Cai, Rui; ChenYang, Yujie; Huang, Zhixing; Han, Benyong
Graphical abstract: Highlights: Eleven tetraethylammonium amino acid ionic liquids were synthesized. [N2222 ][AA]s composed of basic amino acids had stronger alkalinity. [N2222 ][Arg] presented the stronger catalytic capability than [N2222 ][Lys]. Kinetic plots recommended that the reaction pursue the pseudo 1st order kinetics. Abstract: By using amino acids (AAs) as anions, eleven ionic liquids composed of tetraethylammonium (N2222 ) as a cation were synthesized, namely, [N2222 ][AA]s. Their structures were characterized by FT-IR and NMR. The alkalinity of the synthesized AAILs was measured using a pH meter. In the transesterification reaction of soybean oil with methanol, tetraethylammonium arginine ([N2222 ][Arg]) presented the best catalytic capability. The optimal reaction conditions for the transesterification reaction of soybean oil to achieve 98.4% biodiesel conversion were a methanol/oil of 10:1 mol/mol, reaction temperature of 100 °C, catalyst dosage of 20 wt% (based on the oil weight) and reaction time of 60 min. The kinetics study was evaluated and followed the pseudo-first order reaction mechanism, and the activation energy and pre-exponential factor were 34.53 kJ/mol and 1.21 × 10 4 min −1, respectively. [N2222 ][Arg] is a promising, operationally simple, sustainable, biodegradable and possibly renewable catalyst for the conversion of vegetable oil or animal fat into biodiesel.